Isaiah Shembe's hymns and the sacred dance in Ibandla LamaNazaretha - Sithole, Nkosinathi (Studies of religion in Africa, 2016)
Introduction -- Beyond African nationalism : Isaiah Shembe and his hymns -- The Bible, the hymns, and Shembe's sense of self -- The sacred dance and the question of resistance -- Virginity, sexual abstinence and the maidens' rituals -- Male circumcision, marriage and the notion of (in)completeness -- Dress codes and the poetics of performance in the sacred dance -- Conclusion